Konversi Limbah Padat Sagu Menjadi Bioetanol Dengan Proses Hydrolysis Dan Fermentasi Menggunakan Saccharomyces Cerevisiae - Adriani Lestari; Chairul Chairul; Sunarno Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The high reliance on fossil fuels such as crude oil, coal, and gas - causes exhaution on fossil resources ( crude oil, natural gas, and coal). Therefore, to resolve the fossil-fuel dependency, sago solid waste is converted into bioethanol as the renewable energy. On this research, the process of sago pulp fermentation is done by hydrolysis process and fermentation with the use of Saccharomyces cerevisiae as the yeast. The aim of this research is to determine the effect of temperature and time on the hydrolysis process producing glucose and to study the glucose fermentation from hydrolysis into bioethanol from Saccharomyces cerevisae. The hydrolysis process produced glucose with of time of 60 minutes and temperature of 125oC, 135oC and 1450C. Fermentation was done in 2L fermentors for 5 days. The sulfuric acid hydrolysis increases bioethanol levels from sago pulp. The higher the temperature with the increasing time of the process, the higher the glucose concentration will be resulted. The highest glucose was obtained at a temperature of 145 with 60 minutes time which is 24.20 g / L. Sago pulp fermentation process produced a maximum condition at 96-hour fermentation with bioethanol levels of 13%. Keywords: bioethanol, hydrolysis, sago, saccharomyces cerevisiae, fermentation